Identification and mapping of stakeholder roles in the development of local wisdom-based tourism villages in Cikolelet tourism village, Serang, Indonesia - Rahmawati, Rahmawati; Purnaweni, Hartuti; Warsono, Hardi; Yuniningsih, Tri (Edelweiss Applied Science and Technology, 2025)
Local wisdom is a promising tourist attraction in the development of tourism villages. Prosperous tourist villages with local wisdom are stable and developed tourist villages (Bali and Yogyakarta). Meanwhile, other tourist villages that promote village development with local wisdom in Indonesia have not been widely explored. This is constrained by stakeholders’ understanding of local wisdom and tourist attractions within tourist villages. This study aims to describe and analyze the identification and mapping of stakeholders in developing cultural traditions with local wisdom in Cikolelet Tourism Village. Data were generated from semi-structured in-depth interviews and analyzed using stakeholder theory within a public administration approach. The analysis results show that the identification of interests is divided into heterogeneous segmentations based on the accessibility that stakeholders can reach. Second, stakeholders still do not fully understand the need to develop local cultural traditions as promising tourist attractions for improving the community’s economy. The results of the study recommend forming a community of local tourism actors; the village government can officially initiate stakeholder collaboration so that the contribution of each stakeholder complements the existing limitations in the development of Cikolelet Serang, Indonesia, tourism village.